What makes old-age poverty in East Asian societies so high? - Inhoe Ku; Wonjin Lee; Aya Abe; Zhu Mengbing; Shi Li; Chungyang Yeh; Dongjin Kim (Luxembourg Income Study (LIS), 2022)
This study compares poverty among older adults in China, Japan, Korea, and Taiwan with that in selected Western societies and explores factors contributing to these high levels of poverty among older adults from a comparative perspective. Lower education levels of older people contribute to high poverty among East Asian older people while multigenerational living arrangements work toward lowering the poverty rate. Among income sources, low levels of income from public transfer programs account for high old-age poverty although high levels of market income and private transfer income partly offset this among older people. Meanwhile, taking account of financial assets and home ownership does not change the comparative features of high old-age poverty among East Asian older people. Our analyses suggest that the future prospect of economic well-being among older people in the region largely hinges on the further development of welfare state programs for older people.
Keywords: 330; Armut; Soziale Lage; Ältere Menschen; Vergleich; Ostasien; Westliche Staaten